HUBUNGAN MUAL MUNTAH DENGAN KUALITAS HIDUP PASIEN KANKER YANG MENJALANI KEMOTERAPI - Lanny " Filandy; Sofiana " Nurchayati; Ganis " Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Chemotherapy is a treatment of cancer patients which has some side effects. One of them is nauseous vomit. Nauseous vomit caused by chemotherapy can impair the life quality in physical, psychological, social and environmental. This research was aimed to identify the correlation between the nauseous vomit and the life quality of the cancer patients undergoing chemotherapy. This research was a descriptive correlation research by using retrospective approach. The samples were the 30 cancer patients who had undergone chemotherapy by using purposive sampling technique. The measurement used were the questionnaire which was adopted from the Index Nausea, Vomiting, and Retching (INVR) to measure nauseous vomit and WHOQOL-BREF questionnaire to measure the life quality. The analyses used were univariate analysis and bivariate analysis by using chi square test. The research findings indicated p value = 0,032 < α (0,05). It can be concluded that there was a correlation between the nauseous vomit and the life quality of cancer patients undergoing Chemotherapy. Based on the research findings, it is recommended for nurse to be able to provide the nursing care and management of nauseous vomit of the cancer patients undergoing chemotherapy in order to minimize the excessive nauseous vomit which can cause the life quality decrease. Key words             : cancer, chemotherapy, nauseous vomit, quality life